“Early intervention isn't an option, it's a necessity”: learning from implementation facilitators and challenges from the rapid scaling of an early intervention eating disorders programme in England - Hyam, Lucy; Torkelson, Claire; Richards, Katie; Semple, Amy; Allen, Karina L.; Owens, Jill; Jackson, Aileen; Semple, Laura; Glennon, Danielle; Di Clemente, Giulia; Schmidt, Ulrike (Frontiers in Health Services, 2024)
Introduction: The First Episode Rapid Early Intervention for Eating Disorders (FREED) service has shown promising outcomes for young people with an eating disorder, leading to national scaling and implementation across England. Between 2020 and 2023, the national implementation of FREED was supported by the Academic Health Science Networks (AHSNs), which are publicly funded organisations with the mission to spread innovations at scale and pace. This study aimed to investigate the views and experiences of AHSN programme leads on the national roll-out of FREED and the perceived sustainability of the model. Methods and Results: Semi-structured interviews were conducted with 13 programme leads across the AHSNs with direct experience supporting the national implementation of FREED. Thematic analysis was adopted using a critical realist approach. Initial sub-themes were inductively generated and then organised under seven larger themes representing the domains of the Non-adoption, Abandonment, and Challenges to Scale-Up, Spread and Sustainability (NASSS) framework. Each sub-theme was classified as a facilitator and/or barrier and then each larger theme/domain was assessed for its complexity (simple, complicated, complex). Data analysis revealed 28 sub-themes, 10 of which were identified as facilitators, 13 as barriers, and five as both. Two domains were classed as simple, three as complicated, and two as complex. Sub-themes ranged from illness-related complexities to organisational pressures. Key facilitators included a high-value proposition for FREED and a supportive network. Key barriers included staffing issues and illness-related factors that challenge early intervention. Discussion: Participants described broad support for FREED but desired sustained investment for continued provision and improving implementation fidelity. Future development areas raised by participants included enlarging the evidence base for early intervention, increasing associated training opportunities, and widening the reach of FREED. Results offer learning for early intervention in eating disorders and the scaling of new health initiatives.